Deception Processing by Third-Party Observers: The Role of Speaker Intent. Issue 5 (October 2019) - Meek, Scott W.; Bunde, James; Phillips-Meek, Michelle C.; Vendemia, Jennifer M. C.
Deception studies typically focus on the deceiver (or the deceived), with lie detection of paramount concern. Consequently, little attention has been paid to the experience of third-party observers of deceptive communications. In the current study, therefore, we investigated the impact of deception priming on the subsequent information processing of outsiders, with a primary focus on the intent to deceive. Participants read pairs of stories (A and B) depicting everyday interpersonal interactions. In Story A, a phrase was rendered truthful, intentionally deceptive, or unintentionally misleading by context. In Story B, this same phrase was initially presented ambiguously, but followed by a sentence revealing it to be intentionally deceptive. Reading about an intentionally deceptive (as opposed to truthful) speaker (Experiment 1) and an unintentionally deceptive (as opposed to unintentionally misleading) speaker (Experiment 2) in Story A primed faster reading of the "deception" sentence in Story B. These results support the possibility of deception priming and suggest that observers are sensitive to intent (and not mere falsity) when exposed to misinformation scenarios.